(untitled) (Social Science Review, 2021)
The paper seeks to analyse the salient features of the kinship structure in Japan and how it plays it is significant role to form the traditional Japanese values. The paper also tries to analyse the changing nature of the kinship system in contemporary Japanese society from its traditional family (IE) system. The paper follows the qualitative method of research where the data has been collected from both academic and non-academic sources. By analysing the kinship structure of different periods in Japan, the paper finds that during the IE family system of the Tokugawa period, Japan gives less weight to kinship relations than other Asian countries. The feeling on son, either related to blood or adopted, marks the major distinction with other societies to find out the kin and non-kin. Following the IE system, the paper finds another two major events behind the weaken kinship structure in Japan: the emergence of koseki since the Meiji restoration and the rise of corporate culture during the contemporary period. Social Science Review, Vol. 37(2), Dec 2020 Page 105-124